Construção de umchecklist para diagnóstico rápido de pré-eclâmpsia nas urgências obstétricas - Franzon, Verediana Horvatich (2024)
Introduction: Pre-eclampsia is a complex obstetric condition with a high impact on maternal and neonatal morbidity and mortality. Globally it continues to be a challenge in clinical practice, especially in obstetric emergencies, due to a lack of standardized instruments. Despite advances, early diagnosis and effective management of pre-eclampsia remain critical, justifying the need for a specific instrument for its rapid identification and treatment. This study aims to fill the gap in quick diagnosis of pre-eclampsia in obstetric emergency services. Objective: building and validating a comprehensive and accessible tool to assist in the immediate diagnosis of pre-eclampsia. Method: This study was conducted in three distinct steps. Initially, a detailed literature review was carried out as basis for the checklist formulation. Afterwards, the instrument was developed and validatedvirtually by a group of highly qualified specialists in obstetrics and maternal health with the purpose of improving clinical results and ensuring quality of care and patient safety. Validation of the checklist content was carried out using Content Validity Index, with established criterion of 80% for the validity of the items. Furthermore, instrument reliability was evaluated using Cronbach’s alpha and McDonald’s Omega estimations, ensuring its internal consistency and methodological quality.Results: the study resulted in the formulation of an instrument in the form of a specific checklist for assessing pregnant women with suspected pre-eclampsia/ eclampsia. Content validation demonstrated that four items were valid, whereas two others require revision. Additionally, the statistical analyzes carried out demonstrated good internal consistency of the instrument, strengthening its methodological robustness.Conclusion: the checklist instrument developed in this study represents a substantial contribution to clinical practice, offering a structured and effective approach to assessing and managing pregnant women with suspected pre-eclampsia/ eclampsia. Its implementation can improve obstetric outcomes and reduce complicationsassociated with this complex clinical condition, promoting early and appropriate intervention and, consequently, a significant improvement in quality of obstetric care and the safety of the binomial.